Adaptive predictive controller using orthonormal series functions - Oliveira, Gustavo H.C.; Amaral, Wagner C.; Favier, Gerard (Zielona Góra: Uniwersytet Zielonogórski)
A constrained adaptive predictive control method that uses uncertain process modelling based on orthonormal series functions is considered. Such unstructured modelling is described as a weighted sum of orthonormal functions using approximate information about the time constant of the process. The orthonormal series functions model can thus be used to derive a j-step-ahead output prediction according to the constrained adaptive predictive control law.
Keywords: model-based predictive control; adaptive control; uncertain process; orthonormal series functions